RESPON PERTUMBUHAN SAGU (Metroxylon sagu Rottb) DENGAN PERENDAMAN ZAT PENGATUR TUMBUH IBA - Kamsia Dorliana Sitanggang (JURNAL AGROPLASMA, 2020)
Sago is a plant produces high carbohydrate source. The problem of sagoo propagation by generative are limited number of seeds and low germination. Vegetative propagation of sago can be done through sago tillers, however, the very slow root growth will affect the ability of the sago to survive. One way to accelerate root growth is by administering IBA growth regulators. This study aims to determine the response to the growth of sago saplings by immersing IBA (0, 25, 50, 75) ppm. The results showed that the highest percentage of living plants was found in the 25 ppm IBA immersion treatment with the percentage of live tillers 88.89%. For the parameters of the number and length of roots and the highest plant height was also found in the 25 ppm IBA immersion treatment with an average number of roots of 6.7, 12.43 cm of root length and an average plant height of 49 cm.